Reverse staining method of polyacrylamide gels by imidazole-zinc salts for - Javanzad, Shabnam; Bolhassani, Azam; Doustdari, Fatemeh; Hashemi, Mehrdad; Movafagh, Abolfazl (Archives of Advances in Biosciences, 2013)
The human papillomavirus L1 major capsid protein (HPV L1), the basis of the current vaccines, self-assembles into virus-like particles (VLPs). Herein, we describe the expression and purification of recombinant HPV16 L1 in E. coli system. The L1 protein was generated in a fused form using an inducible expression system. The recombinant GST-L1 fusion protein migrated as a 82 kDa protein in SDS-PAGE. The L1 proteins formed inclusion bodies which were purified by Zn+2 reverse staining of sodium dodecyl sulfate polyacrylamide gels (SDS-PAGE) as a sensitive detection method. In western blotting, the existence of a 82 kDa band for GST-L1 protein was confirmed by anti-HPV16 L1 monoclonal antibody Camvir 1. The purified protein fraction was concentrated by ultrafiltration and dialyzed against PBS. This study has implications for the development of L1 protein purification as well as chromatographic separation used by other studies. Indeed, we could present a simple method to purify L1 protein in E. coli.